Prosedur Jasa Keagenan Kapal Dengan Sistem Inaportnet Untuk Efisiensi Waktu - Kusharyanto Kusharyanto; Ageng Premadi; Susiarni Magdalen; Desy Sakinatu Syifa (Departemen Teknik Kelautan Universitas Hasanuddin, 2023)
This research aims to know agency service implementation flow by inaportnet system. This research use qualitative descriptive design. This research is conducted in the port of PT. Pelindo II (Persero) and PT. Adi Bahari Nuansa Banten. Method of collecting data such as literature review, documentation, observation and interview. The result of this research is agency service implementation flow with inaportnet system and vessel management system (VMS) by PT. Adi Bahari Nuansa is complicated by operational staff of PT. Adi Bahari Nuansa. Agency service with inaportnet system and Vessel Management System (VMS) have a delays in sending ship document, so that hampering the entire process of agency activities using the inaportnet system and vessel management system (VMS). In addition, making billing for payment of signs, and vessel traffic system money has not been able to use the inaportnet system, so that the implementation of agency services not run effectively and optimally.